Dove/non dove. "Il parco virtuale": una nota esplicativa - Diego Salvadori (Lea, 2017)
In this article we present the database Dove/nondove, which aims aims to collect and list the texts of female authors who’ve wrote about places and spaces. The goal is to create a global hypertext, monitoring the evolution of specific themes (landscape and environment, pollution and ecological crisis, human non-human relation) in the Feminine literature.